Comparison of the Prevalence of Metabolic Disease Between Two Types of Urbanization in China - Han, Bing; Chen, Yi; Cheng, Jing; Li, Qin; Zhu, Chunfang; Chen, Yingchao; Xia, Fangzhen; Wang, Ningjian; Lu, Yingli (Frontiers in Endocrinology, 2018)
Objective: China is experiencing the world’s largest urbanization. There are two primary types of urbanization in China: rural-to-urban migration and in situ urbanization, represented by Zhejiang Shangyu (SY) and Jiangsu Nanjing (NJ), respectively. Our aim is to compare metabolic changes between different types of urbanization in China. Methods: This is a cross-section study derived from the SPECT-China 2014 study. This study includes subjects and metabolic parameters from SY and NJ. Furthermore biochemical and anthropometric indexes were taken into consideration and compared between the areas of interest. Results: The prevalence of diabetes, prediabetes and healthy subjects was 6.5%, 17.9% and 75.7% in SY, and 16.0%, 31.0% and 53.0% in NJ, respectively. Occupational composition indicated that the industry and agriculture accounted for 77.9% and 32.0% in SY and NJ, respectively. FPG in SY was higher than in NJ however, HbA1c in SY was lower than in NJ. There was a significant difference in nonalcoholic fatty liver disease (NAFLD) and healthy subjects between SY and NJ (P<0.05). Significant differences were also found in body mass index (BMI), waist circumference (WC) and hip circumference (HC) between these two places (P<0.001). Logistic regression analysis showed that the prevalence of prediabetes, diabetes, overweight, obesity and dyslipidemia in NJ was higher than in SY. Conclusions: In situ urbanization has notably changed occupational distribution. The prevalence of diabetes, obesity, and NAFLD were increased in rapid urbanized areas. Thus, more attentions should be paid in rapid urbanization areas to reduce the prevalence of metabolic disease.